Penerapan Model Pembelajaran Saintifik untuk Meningkatkan Motivasi dan Hasil Belajar Matematika Siswa Kelas VIII.C SMP Negeri 12 Mataram - Istiroha, Istiroha (TSAQOFAH, 2022)
The purpose of this study was to find out: 1) How did the motivation to learn Mathematics increase after applying the scientific learning model to class VIII.C students of SMP Negeri 12 Mataram even semester of the 2021/2022 Academic Year; 2) How did the learning outcomes of Mathematics increase after the scientific learning model was applied to class VIII.C students of SMP Negeri 12 Mataram even semester of the 2021/2022 Academic Year. The research subjects totaled 32 students consisting of 17 male students and 15 female students. The subjects that were the target of the research were Mathematics. Based on the results of the achievement of action research indicators in class VIII.C of SMP Negeri 12 Mataram which were carried out in three cycles, it can be concluded that the learning outcomes of class VIII.C students of SMP Negeri 12 Mataram for the academic year 2021/2022, with a scientific learning model can be improved with the final results research is the class average before the action 67.94 or 53.13% classical completeness, to 72.63 or 65.63% classical completeness in cycle I, increased to an average of 74.69 or 81.25% in cycle II and experienced an increase to an average test of 76.94 or 90.63% in cycle III. From the results of student observations it was shown that there was an increase in student motivation which in cycle I obtained a score of 2.93 or Less to 3.33 or Enough in cycle II and 3.92 or Good in cycle III. The increase in student activity in learning mathematics is supported by the increase in teacher activity in maintaining and improving the learning atmosphere using the scientific learning model, this can be seen from the observations of teacher activities where in cycle I a score of 22 or 61.10% was obtained, becoming 26 or 72, 23% in cycle II and increased to 33 or 86.12% in cycle III.